2010
DOI: 10.1021/jf103086e
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Sorption of Diverse Volatiles by Saccharomyces cerevisiae Lees during Sparkling Wine Aging

Abstract: The volatile profile of sparkling wine is influenced by the retention and release of volatile compounds by lees during the aging process. Here we attempted to identify the volatiles that are most retained by lees in aging conditions and to study how their sorption varies during aging. We estimated the lees sorption capacity for several representative volatile compounds in sparkling wine samples at a range of time points during aging by assessing the volatiles sorbed on the lees surface and those present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…Conversely, the concentration of ethyl esters of fatty acids which are described as fruity and pleasant aromatic compounds significantly decreased after nine month of aging, contributing to the overall loss of "fresh", "fruity" and "flowery" notes on aged wines [18]. This peculiar behavior of fatty acids and ethyl esters can be attributed to the adsorption by the lees [6], and the release during autolysis [1,19].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Conversely, the concentration of ethyl esters of fatty acids which are described as fruity and pleasant aromatic compounds significantly decreased after nine month of aging, contributing to the overall loss of "fresh", "fruity" and "flowery" notes on aged wines [18]. This peculiar behavior of fatty acids and ethyl esters can be attributed to the adsorption by the lees [6], and the release during autolysis [1,19].…”
Section: Resultsmentioning
confidence: 96%
“…The first fermentation transforms the grape must into a base wine, in a process that is very similar to that used for high quality white wines. The second fermentation, "prise de mousse", occurs in the bottles after the addition of a "tirage solution" that includes yeast, sucrose, nutrients, and sometimes bentonite [1][2][3], and is followed by a biological aging in contact with lees in anaerobic conditions for 6-12 months [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Gallardo-Chac on et al (2009) determined the volatile compounds retained by lees during the second fermentation of sparkling wines and found that esters, aldehydes and terpenes were retained by the lees surface. Sorption depends not only on the physicochemical characteristics of the volatile compounds but also on the structure of the yeast cell walls, hence the retention of volatile compounds by the lees surface can be reversible and the volatile composition of these wines can change over long aging time (Gallardo-Chac on et al, 2010). Therefore, the final aging time will determine the type and amount of the volatile compounds present in sparkling wines (Francioli et al, 2003; Table 1 Volatile compounds of the sparkling wines at the different aging times: T9, T18, T30: nine, eighteen, thirty months of aging on lees; 12 MB: twelve months in bottle after disgorging.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the potential significance of aromatic absorption by lees should not be overlooked (Gallardo-Chacón et al, 2010). Some, such as the release of glucans, amino acids, peptides, and mannoproteins are clearly associated with yeast autolysis.…”
Section: Second Fermentationmentioning
confidence: 99%